Implementation of the Merdeka Curriculum in Building the Values of Religious Tolerance at SMP Piri 2 Yogyakarta - Adira, Hukma Fikria (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Indonesia is a highly pluralistic nation in every way, including religion. Due to this, Indonesia urgently requires multireligious schools in order to provide an inclusive learning atmosphere for children of all religious origins. In multireligious schools, the Merdeka Curriculum can serve as an excellent bridge to foster tolerance, appreciation, and understanding of religious diversity. The purpose of this study is to ascertain how Piri 2 Middle School in Yogyakarta may incorporate an autonomous curriculum to foster ideals of religious tolerance. The three steps of data analysis used in this qualitative study are data condensation, data presentation, and conclusion drawing. The procedures were developed by Johnny Saldana, A. Michael Huberman, and Matthew B. Miles. The study's findings demonstrate the three methods used by SMP Piri 2 Yogyakarta to execute the Merdeka curriculum and instill the ideals of religious tolerance. First, by taking an inclusive stance; second, by utilising multicultural teaching resources; third, by fostering collaborative learning environments and encouraging active participation from educators, parents, and community members. Schools may foster an inclusive environment, promote respect for cultural diversity, broaden students' worldviews, and produce a generation that is accepting and considerate of cultural differences by implementing these measures.Indonesia adalah negara yang sangat plural dalam segala hal, termasuk agama. Oleh karena itu, Indonesia sangat membutuhkan sekolah multiagama untuk memberikan suasana pembelajaran inklusif bagi anak-anak semua agama. Di sekolah multi agama, Kurikulum Merdeka dapat menjadi jembatan yang sangat baik untuk menumbuhkan toleransi, penghargaan dan pemahaman terhadap keberagaman agama. Tujuan penelitian ini adalah untuk mengetahui bagaimana SMP Piri 2 Yogyakarta dapat menerapkan kurikulum otonom untuk menumbuhkan cita-cita toleransi beragama. Tiga langkah analisis data yang digunakan dalam penelitian kualitatif ini adalah kondensasi data, penyajian data, dan penarikan kesimpulan. Prosedur ini dikembangkan oleh Johnny Saldana, A. Michael Huberman, dan Matthew B. Miles. Hasil dari penelitian ini menunjukkan, bahwa implementasi kurikulum merdeka dalam membangun nilai-nilai toleransi beragama di sekolah SMP[DWAM1]Â Piri 2 Yogyakarta dilakukan dengan tiga cara. Pertama melalui pendekatan inklusif, kedua dengan menggunakan bahan ajar yang multikultural, ketiga dengan pembelajaran kolaboratif, dan keterlibatan aktif dari guru, siswa, orang tua, dan komunitas. Dengan mengadopsi strategi-strategi tersebut, sekolah dapat menciptakan lingkungan yang inklusif, mendorong penghargaan terhadap keberagaman budaya, memperluas pemahaman siswa tentang dunia, dan membentuk generasi yang toleran dan menghargai perbedaan budaya.